Osmanlı-İran ilişkileri : sınır ve siyaset - Tikici, Naci (My University, 2022)
OSMANLI-İRAN İLİŞKİLERİ: SINIR VE SİYASET Bu çalışma, Osmanlı-İran siyasi ilişkilerine farklı bir bakış açısı getirmekte ve iki ülke ilişkilerini, sınır sorunlarını merkeze alarak incelemeyi amaçlamaktadır. Bu incelemenin her bir bölümü, iki ülke ilişkilerini farklı bir çerçeveden anlama ve anlatma çabası içerisinde olduğundan, bugüne kadar alışıla gelmiş yorumlara ihtiyatla yaklaşmaktadır. Araştırma sonuçları, iki ülkenin sorunlu siyasi ilişkilerinin üç temel ilkeden oluştuğunu öne sürmektedir. Birinci ilke, Osmanlı yönetiminin doğuda kendi doğal sınırlarına uzanma ve İran ile yeni bir sınır oluşturup, İran’ı bu sınırların ötesinde tutma çabasıdır. Bu çaba, Yavuz Sultan Selim (1512-1520) ve Kanuni Sultan Süleyman (1520-1566) ile IV. Murat (1623-1640), Şah Abbas (1587-1629), Nadir Şah (1736-1747) ve Feth Ali Şah (1797-1834) dönemi olaylarında açıkça müşahede edilmektedir. İkinci ilke, ülke yöneticilerinin zaman zaman imparatorluk ordusuyla sınır ötesinde bir güvenlik kuşağı oluşturma ve kendi sınırlarını sınır ötesinden koruma gayretine dairdir. Ülke yöneticilerinin, 1578, 1723, 1905 ve 1914 İran seferlerinde bu gaye içinde oldukları görülmektedir. Üçüncü ilke ise; Osmanlı yöneticilerinin tüm zamanlar için, İran ile kendi sınırları arasında bir tampon bölge oluşturma gerçeğine işaret etmektedir. ran, sınır, sınır komisyonu, sınır müzakereleri, tahdid-i hudud.

OTTOMAN-IRANIAN RELATIONS: BORDER AND POLITICS This study brings a different perspective to Ottoman-Iranian political relations and aims to examine the relations of the two countries by focusing on border problems. Since each section of this study seeks to understand and explain the relations between the two countries from a different framework, it approaches the usual interpretations with caution. The result of the research suggest that the problematic political relations of the two countries consist of three basic principles. The first principle is the effort of the Ottoman administration to reach its natural borders in the east and to create a new border with Iran and keep Iran beyond these borders. This effort is clearly observed in the events of the period of Yavuz Sultan Selim (1512-1520), Sultan Suleyman (1520-1566), IV. Murat (1623-1640), Shah Abbas (1587-1629), Nadir Shah (1736-1747) and Fath Ali Shah Qajar (1797-1834). The second principle is related to the efforts of the rulers of the country to create a security belt across the border with the imperial army at various times and to protect their own borders from across the border. It is seen that the rulers of the country had this aim in the 1578, 1723, 1905 and 1914 Iranian campaigns. The third principle points to the fact that the Ottoman rulers efforts to create a buffer zone between Iran and their borders for all time. ran, border, border commission, border negotiations, border restriction..
Ottoman-Iranian relations : border and politics
Keywords: border; border commission; border negotiations; border restriction; Dış ilişkiler; Foreign relations; History; Iran; İran; Osmanlı İmparatorluğu; Ottoman Empire; sınır; sınır komisyonu; sınır müzakereleri; tahdid-i hudud; Tarihi; Turkey; Türkiye